TOKOH PANAKAWAN SEBAGAI SARANA PEMBANGUN WACANA KRITIK SOSIAL PADA PERTUNJUKAN WAYANG KULIT DI MEDIA YOUTUBE - Prakoso, Imam (Widyaparwa, 2023)
The presence of panakawan in the shadow puppet show with its own dynamics. Now they are no longer limited as complementary instruments in the dramatic structure of wayang performances. Panakawan is now also interpreted as a reformer in wayang presentation, such as the use of characters who are naive, witty, and sometimes talk as they are. The identification of his figure which is interpreted as a small people also provides a new color for the development of wayang kulit performances. This study discusses the discourse of social criticism that is built from the language style of the panakawan figures. The style of language that is seen is from the use of figure of speech, the strategy of sentence structure, and the selection of diction. The results of this study indicate that there is social criticism that discusses problems in the realm of development, education, law, dirty political behavior of public officials, culture, and morals. The criticism is conveyed both explicitly and implicitly through the use of figure of speech, scrutinizing sentence structure, and choice of diction. All these criticisms were conveyed by panakawan who were represented as small people against other figures such as kings or gods who were represented as leaders or public officials.Kehadiran panakawan di dalam pertunjukan wayang kulit diwarnai dengan dinamikanya tersendiri. Kini mereka tidak lagi sebatas instrumen pelengkap di dalam struktur dramatik pertunjukan wayang. Panakawan kini juga dimaknai sebagai sosok pembaharu dalam sajian wayang, seperti pe-manfaatan karakter yang lugu, jenaka, dan terkadang berbicara apa adanya. Identifikasi terhadap sosoknya yang dimaknai sebagai rakyat kecil juga memberikan warna baru bagi perkembangan pertunjukan wayang kulit. Penelitian ini membahas tentang wacana kritik sosial yang dibangun dari gaya bahasa pada tokoh panakawan. Adapun gaya bahasa yang dilihat yaitu dari pemanfaatan majas, penyiasatan struktur kalimat, serta pemilihan diksi. Hasil penelitian ini menunjukkan bahwa terdapat kritik sosial yang membahas permasalahan dalam ranah pembangunan, pendidikan, hukum, perilaku politik kotor para pejabat publik, budaya, serta moral. Kritik tersebut disampaikan baik secara eksplisit maupun implisit melalui pemanfaatan majas, penyiasatan struktur kalimat, serta pilihan diksi. Seluruh kritik tersebut disampaikan oleh panakawan yang direpresentasikan sebagai rakyat kecil terhadap tokoh lain, seperti raja atau dewa yang direpresentasikan sebagai pe-mimpin atau pejabat publik.